La gastronomía y la rentabilidad de los comerciantes del Mercado la Merced de la ciudad de Riobamba - Manya Colcha, Jennifer Tatiana (2024)
BSTRACT The investigative work aimed to determine the impact of gastronomy on the profitability of the merchants at the La Merced market in the city of Riobamba. The methodology used to carry out the research was the hypothetical-deductive method. A hypothesis was formulated and corroborated as the research progressed. The research approach was descriptive and non-experimental, and for this reason, the La Merced market was chosen as the study object. Regarding the research results, it was observed that gastronomy significantly influenced profitability by offering a broader perspective on how potential customers reacted to gastronomic experiences and their quality and innovation. It not only allowed understanding of emotional responses but also provided tools to optimize resources and improve culinary preparation processes, satisfying the needs of both customers and tourists. Gastronomy drove the design of experiences where consumers were captivated by the preparation, presentation, taste, and aroma of typical dishes, thus achieving positive profitability. Similarly, in the preparation of this report, the survey technique was applied to samples of potential customers and gastronomic merchants at the La Merced market in the city of Riobamba. A questionnaire with closed questions was used to collect information. The collected data was processed using tables and statistical graphs in Microsoft Excel. The hypothesis verification was carried out using SPSS software, which facilitated the management, organization, and analysis of data for easy interpretation. Keywords: Gastronomy, profitability, customers, merchants. Reviewed by: Mgs. Kerly Cabezas ENGLISH PROFESSOR I.D. 0604042382